Estudio del índice de desarrollo gonadal de la concha pata de mula anadara grandis cultivada en granjas camaroneras y obtenidas de pesca comercial - Paredes Correa, Miguel Luis (2011)
The following work was carried out in the camaronera of property of Mrs. Elvia Palacios Gonzales, located in the road Guarumal, kilometer 15, canton Santa Rosa of the County of The Gold. In this investigation the following objectives were had. 1. To evaluate the maturation gonadal of the shell mule (Anadara grandis) paw in captivity, cultivated in baskets in pools camaroneras. 2. To compare the maturation gonadal of Anadara grandis in captivity, with the specimens captured for the commercial sale. In this investigation four baskets were used, with a density of 20 specimens for basket of cultivation that you/they were introduced in a pond with shrimp cultivation, every month the shells of the baskets were sacrificed, to be compared with the copies captured commercially, with the biological same characteristic of the shells of the basket (size averages). The index of development gonadal was evaluated during four months.The shells mule (Anadara grandis) paw in captivity and cultivated in baskets, during the fourth month (March) they presented 70% of gónadas of orange color, and the percentage of females was of 66,7% during the first month (December) the same as the uncertain sex with 66,7% in the second month (January), the grade 0 of development gonadal you presents with 50% during the second month (January). When comparing the captivity shells with those of commercial capture in the first month (December) the orange coloration of the gónadas of the captivity shells, it was bigger with 50%, the percentage of females and of uncertain sex it was same (66,7), while the grade III of development gonadal of the captivity shells went similar to the grade 0 of development gonadal of the shells of commercial capture with 41,7%. while the grade 0 of development gonadal of the captivity shells went similar to the grade 0 of development gonadal of the shells of commercial capture with 50%. In the third month in the captivity shells the grade 0 of development gonadal were bigger (40%). In the fourth month (March), the grade III of development gonadal were of 50% in the shells of commercial capture.